PENYEBARAN HOAKS DI MEDIA SOSIAL ANALISIS DESKRIPTIF KUALITATIF BERITA PENGANIAYAAN RATNA SARUMPAET - Oktafiani Herlina (AKADEMI KOMUNIKASI RADYA BINATAMA, 2019)
This research discusses the spread of hoaks on social media through a qualitative descriptive analysis of the Ratna Sarumpaet’s persecution case. Technological developments have brought the major changes in society. People used to get information from the mainstream media but now they can also get information from social media. Social media can be used to spread the news. Social media users not only become distributors of information but simultaneously become producers of information. In addition to disseminating information from online media, users can also create their own information on social media. Social media is the intermediary for the highest spread of hoaks compared to other media. In the case of spread news of Ratna Sarumpaet’s persecution case, social media namely facebook and twitter became the first media that inform this case. The social and political situation also influenced the wider spread of the news. Social media users can immediately spread the information and even reproduce the information without thinking about the aftermath. The people must be aware of the hoax news and must provide preventive steps by checking and rechecking and also filtering information obtained before spreading the news.